Biomarkers of the brain injuries - the future diagnosis standard in head trauma? - Andreea Elena Bîrlescu; Bianca Hanganu; Andreea Alexandra Hleșcu; Irina Smaranda Manoilescu; Beatrice Gabriela Ioan (Romanian Neurosurgery, 2019)
Acute head trauma is often a clinical challenge in diagnosing the brain damage, assessing its severity and prognosis, and establishing the optimal treatment. Different patients, with brain damage of apparent comparable severity according to the imaging examination, may have different neurological evolution or different response to therapy. Minor traumatic brain injuries can induce a brief loss of consciousness or confusion, are usually benign, but sometimes they cause persistent and progressive brain symptoms in the long run. However, at present, there are no reliable methods that can diagnose properly minor traumatic brain injuries. Biomarkers of the brain injuries allow the monitoring of both physiological and pathological processes. The identification of such biomarkers could allow a better understanding of the pathological processes involved in traumatic brain injuries, their diagnosis, prognosis and may facilitate the establishment of a better treatment regimen for these patients. In this article, the authors make a brief review of the literature in which they analyse the biomarkers of the lesions of the various brain structures identified so far, which can be detected in biological fluids (blood, cerebrospinal fluid) and the advantages and limitations of their use in the current medical practice.